Reliability analysis of prestressed concrete bridge girder beam - Kumar, Guna (2005)
Recent studies undertaken in the United States and Europe have shown that there are many highway bridges rated as structurally deficient requiring rehabilitation or replacement due to the increase traffic flow and modern truck loads. The objective of this dissertation is to compare the reliability based load factor for prestressed bridge girders against the deterministic load factor given in six (6) codes namely; BS5400 Pt.2, AASHTO, Canadian Code (OHBDC), Eurocode, Australian Code (Austroads) and JKR specifications. ‘Y5’ prestressed bridge girder with a resistance of 4192kNm assumed to be a constant are considered. The load parameters and the bridge spans are treated as random variables. The statistical parameters are based on available literature and test data. The reliability indices for load factor are calculated by iteration utilizing Monte Carlo simulation. Based upon the results obtained it can be concluded with confidence that in the design of primary highway loads, the load factor given in the codes can be reduced by approximately 10 to 13%. The results also indicate that AASHTO is the most conservative code while BS5400 Pt.2 and Eurocode are the most permissive. This would mean that using BS5400 Pt.2 or Eurocode will result in a cost effective bridge girder beam